THE PLANFORMS OF LOW-ANGLE IMPACT CRATERS IN THE NORTHERN HEMISPHERE OF MARS - Herrick R.R.; Hessen K.K. (My University, 2006)
We have surveyed Martian impact craters greater than 5 km in diameter using Viking and thermal emission imaging system (THEMIS) imagery to evaluate how the planforrn of the rim and ejecta changes with decreasing impact angle. We infer the impact angles at which the changes occur by assuming a sin2Θ dependence for the cumulative fraction of craters forming below angle Θ. At impact angles less than ~40° from horizontal, the ejecta become offset downrange relative to the crater rim. As the impact angle decreases to less than ~20°, the ejecta begin to concentrate in the cross-range direction and a "forbidden zone" that is void of ejecta, develops in the uprange direction. At angles less than ~10°, a "butterfly" ejecta pattern is generated by the presence of downrange and uprange forbidden zones, and the rim planform becomes elliptical with the major axis oriented along the projectile's direction of travel. The uprange forbidden zone appears as a "V" curving outward from the rim, but the downrange forbidden zone is a straight-edged wedge. Although fresh Martian craters greater than 5 km in diameter have ramparts indicative of surface ejecta flow, the ejecta planforms and the angles at which they occur are very similar to those for lunar craters and laboratory impacts conducted in a dry vacuum. The planforms are different from those for Venusian craters and experimental impacts in a dense atmosphere. We interpret our results to indicate that Martian ejecta are first emplaced predominantly ballistically and then experience modest surface flow. © The Meteoritical Society, 2006.